2021
DOI: 10.2106/jbjs.21.00375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Femoral and Acetabular Version on Outcomes Following Hip Arthroscopy

Abstract: Background: Torsional hip deformities are common among patients undergoing hip arthroscopy. However, recent studies have suggested conflicting outcomes following arthroscopy in the setting of abnormal hip version. The purpose of this study was to systematically evaluate the literature and determine the impact of femoral and acetabular version on patient-reported outcomes following primary arthroscopic hip surgery.Methods: This study was conducted in accordance with the PRISMA (Preferred Reporting Items for Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…13 Variations in FV are becoming increasingly recognized as contributing factors to the development of hip pain in patients with FAI. 14 However, two recent systematic reviews investigated the influence of FV for the outcome of hip arthroscopy, 15,16 and they reported that patients with normal FV and patients with femoral retroversion (FV < 5°) exhibited similar outcome scores, and similar failure rates at short-term follow-up. 15 Another recent systematic review reported a frequency of abnormal FV of 51% in patients with symptomatic FAI.…”
Section: Investigated Abnormalities Of Femoral Version (Fv) Femoral R...mentioning
confidence: 99%
“…13 Variations in FV are becoming increasingly recognized as contributing factors to the development of hip pain in patients with FAI. 14 However, two recent systematic reviews investigated the influence of FV for the outcome of hip arthroscopy, 15,16 and they reported that patients with normal FV and patients with femoral retroversion (FV < 5°) exhibited similar outcome scores, and similar failure rates at short-term follow-up. 15 Another recent systematic review reported a frequency of abnormal FV of 51% in patients with symptomatic FAI.…”
Section: Investigated Abnormalities Of Femoral Version (Fv) Femoral R...mentioning
confidence: 99%
“…The impact of the femoral version on hip function and pathology has become increasingly recognized in the past decade (10,11). A recent cross-sectional study of 538 symptomatic hips suggested an incidence of severe femoral version abnormalities in 17% of patients (10) planning of a femoral rotational osteotomy, the authors concluded that these metrics can help position the greater trochanter appropriately in the axial plane, resulting in normal functional antetorsion (51).…”
Section: Version/torsionmentioning
confidence: 99%
“…The impact of the femoral version on hip function and pathology has become increasingly recognized in the past decade ( 10 , 11 ). A recent cross-sectional study of 538 symptomatic hips suggested an incidence of severe femoral version abnormalities in 17% of patients ( 10 ).…”
Section: Femurmentioning
confidence: 99%
See 1 more Smart Citation